Menopause and facial skin microbiomes: a pilot study revealing novel insights into their relationship - Pagac, Martin Patrick; Stalder, Martin; Campiche, Remo (Frontiers in Aging, 2024)
The skin microbial composition is affected by age. Previous studies reported skin microbiome diversity shifts between elderly and significantly younger subjects. Some studies implied that menopausal status, which is inherently linked to age, could be associated with changes in skin microbial compositions. Nevertheless, the influence of menopausal status on skin microbiome profiles while minimizing the impact of aging-associated changes in skin parameters still needs further clarification. We performed an observational study on healthy Caucasian female volunteers, which were grouped according to their pre-or postmenopausal status. Bacterial community structures on facial skin were analyzed using 16S rRNA gene sequencing. Cutometer® measurements were performed to evaluate aging-associated changes in facial skin biophysical properties. Relative abundances of lipophilic Cutibacterium genera were decreased, and bacterial diversities were increased in skin samples of postmenopausal volunteers. The mean age difference between examined groups in this study was 12.4 years only. Accordingly, Cutometer® measurements revealed no differences in aging-associated skin biophysical parameters between pre-and postmenopausal groups. Consequently, no correlation was detected between Shannon diversity and measured age-dependent biomechanical properties of facial skin. These findings are in line with previous studies, which investigated the wide-ranging impact of chronological aging on skin microbial communities. However, this work reports for the first time a direct association between menopausal status and facial microbiomes on skin of similarly aged study participants, and hence uncouples aging-associated skin biophysical parameters, such as viscoelastic properties, from the equation. These findings open avenues for the development of microbiome-targeting strategies for treatment of menopause-associated skin disorders.